Milk Production, Milk Composition, Milk Fatty Acid Profile and Nutrient Digestibility of Mehsana Goats Fed Sunflower (Helianthus annus) Oil - Raut, A. S.; Patil, S. S.; Pawar, M. M.; Patel, M. P.; Gupta, J. P.; Modi, C. P. (International Journal of Bio-resource and Stress Management, 2024)
A study was conducted during the month of December, 2020 to January, 2021 at Livestock Research Station, Kamdhenu University, Sardarkrushinagar, Gujarat (385506), India to evaluate the effect of dietary sunflower oil supplementation on milk yield, milk fatty acid profile and nutrient digestibility of Mehsana goats. Eighteen lactating Mehsana goats were randomly divided into three treatment groups, viz. Basal diet (control), Basal diet+25 g animal-1 day-1 of sunflower oil and Basal diet+50 g animal-1 day-1 of sunflower oil for a period of 60 days. No significant differences (p>0.05) were found in milk yield in terms of kg d-1, 4% fat corrected milk and energy corrected milk among the treatment groups. The milk constituents and their yields were not affected due to dietary inclusion of sunflower oil. Sunflower oil feeding at the dose of 50 g d-1 increased (p<0.05) concentration of milk short chain fatty acids and polyunsaturated fatty acids in the milk of goats. The intake and digestibility of nitrogen free extract was increased in sunflower oil supplemented groups. The intake and digestibility of dry matter, organic matter, crude protein, ether extract and crude fibre were similar (p>0.05) among the treatment groups. it may be concluded that supplementation of sunflower oil at the dose rate of 25 and 50 g d-1 did not affect feed intake, milk yield, milk constituents and nutrient digestibility in lactating Mehsana goats. However, dietary 50 g d-1 of sunflower oil significantly increased concentration of milk short chain fatty acids and polyunsaturated fatty acids in goats.